2021
DOI: 10.1038/s41598-021-99458-8
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the effect of electrocatalytic performance boost during hydrogen evolution reaction on free-standing SWCNT film electrode

Abstract: Large-scale sustainable hydrogen production by water electrolysis requires a highly active yet low-cost hydrogen evolution reaction (HER) electrocatalyst. Conductive carbon nanomaterials with high surface areas are promising candidates for this purpose. In this contribution, single-walled carbon nanotubes (SWCNTs) are assembled into free-standing films and directly used as HER electrodes. During the initial 20 h of electrocatalytic performance in galvanostatic conditions, the films undergo activation, which re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Both spectra display similar features having signals at 706.6 and 719.7 eV, which could be assigned to metallic Fe 2p 3/2 and Fe 2p 1/2 , respectively . The peaks at 711.5 and 724.6 eV are attributed to Fe 2p 3/2 and Fe 2p 1/2 in Fe 2 O 3 and other Fe­(III) compounds, respectively . The spectra clearly indicate the change in the relative intensity of the signals after electrochemical measurements.…”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…Both spectra display similar features having signals at 706.6 and 719.7 eV, which could be assigned to metallic Fe 2p 3/2 and Fe 2p 1/2 , respectively . The peaks at 711.5 and 724.6 eV are attributed to Fe 2p 3/2 and Fe 2p 1/2 in Fe 2 O 3 and other Fe­(III) compounds, respectively . The spectra clearly indicate the change in the relative intensity of the signals after electrochemical measurements.…”
Section: Resultsmentioning
confidence: 76%
“…The X-ray Photoelectron Spectroscopy (XPS) spectra (Figure f) of Fe 2p were collected before and after electrolysis to study the effect of HER on the chemical states of iron present in the electrode. Both spectra display similar features having signals at 706.6 and 719.7 eV, which could be assigned to metallic Fe 2p 3/2 and Fe 2p 1/2 , respectively . The peaks at 711.5 and 724.6 eV are attributed to Fe 2p 3/2 and Fe 2p 1/2 in Fe 2 O 3 and other Fe­(III) compounds, respectively .…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Kordek-Khalil et al discussed the HER behavior of a freestanding SWCNT film catalyst in an alkaline medium, which shows a 225 mV overpotential and 135 mV dec −1 Tafel slope. 61 Pal et al examined the HER behavior via band modulation of covalently connected CNTs in an acidic medium, 62 showing the overpotentials of 480 and 300 mV for SWCNT-OH and 3D MWCNTs, respectively. In the present work, the In 2 O 3 /SWCNT-4 heterostructure catalyst shows the lowest overpotential of 141 mV, a low Tafel slope of 107.7 mV dec −1 , and outstanding stability for 24 h. It is also concluded that the In 2 O 3 /SWCNT-4 heterostructure catalyst shows excellent bifunctional electrocatalytic activities.…”
Section: Resultsmentioning
confidence: 99%
“…Kordek-Khalil et al. discussed the HER behavior of a free-standing SWCNT film catalyst in an alkaline medium, which shows a 225 mV overpotential and 135 mV dec –1 Tafel slope . Pal et al examined the HER behavior via band modulation of covalently connected CNTs in an acidic medium, showing the overpotentials of 480 and 300 mV for SWCNT-OH and 3D MWCNTs, respectively.…”
Section: Results and Discussionmentioning
confidence: 99%